Platelet to lymphocyte ratio predicts all-cause mortality in patients with carotid arterial disease - Tek Mujgan; Çetin Mehmet Serkan; Diker Erdem; Çelebi Savaş; Amasyali Basri; Berkalp Berkten (Sciendo, 2019)
Background. Platelet to lymphocyte ratio (PLR) has been demonstrated as a risk and prognostic marker in many of cardiovascular diseases. A relationship between PLR and severity of carotid stenosis has been shown. The aim of our study was to investigate the relationship between PLR and all cause mortality in patients with carotid arterial disease.